(untitled) (Journal of the College of Basic Education, 2022)
the teachers’ point of view To achieve the goal of the research, the researcher prepared a questionnaire. consisting of (62) items to identify the reasons for low achievement, each of which represents one of the possible causes of low achievement. Its validity and reliability were verified; The researcher used the descriptive approach in the research. The study sample consisted of (310) teachers and schools, which is approximately (10%) of the total community.